2016
DOI: 10.4238/gmr.15028093
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms of the cyclooxygenase-2 gene and prognosis of hepatocellular carcinoma - a cohort study in Chinese people

Abstract: ABSTRACT. Cyclooxygenase-2 (COX-2) influences carcinogenesis through regulation of angiogenesis, apoptosis, cytokine expression, and immune response suppression. It has been well established that COX-2 is overexpressed in a variety of human cancers, such as hepatocellular carcinoma (HCC). In this study, we aimed to evaluate the association between COX-2 polymorphisms and prognosis of HCC. We genotyped 200 HCC patients of Chinese Han descent for COX-2 gene polymorphisms (-765G>C and -1195G>A) using PCR-RFLP. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Regarding COX-2 expression, the literature data even indicates that COX-2 does not mediate the process of fibrosis[6,29,30], or, contrary, COX-2 plays roles in fibrogenesis and hepatocarcinogenesis via metalloproteinases/mismatch repair proteins MMP-2 and MMP-9 or through activation of β-catenin[3], one of the mediators of epithelial mesenchymal transition[19]. Although COX-2 stimulates HCV replication and HCV stimulates COX-2 expression via oxidative stress[3], we did not find differences between COX-2 expression in patients with or without hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding COX-2 expression, the literature data even indicates that COX-2 does not mediate the process of fibrosis[6,29,30], or, contrary, COX-2 plays roles in fibrogenesis and hepatocarcinogenesis via metalloproteinases/mismatch repair proteins MMP-2 and MMP-9 or through activation of β-catenin[3], one of the mediators of epithelial mesenchymal transition[19]. Although COX-2 stimulates HCV replication and HCV stimulates COX-2 expression via oxidative stress[3], we did not find differences between COX-2 expression in patients with or without hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is an enzyme encoded by the PTGS2 gene, which belongs to the group of endogenous tumor factors that might stimulate genesis and progression of HCC[6]. There are three isoforms: constitutive COX-1, inducible COX-2, and COX-3[3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are zinc metalloproteases that degrade ECM collagens, which are important in tissue remodeling and repair during development and inflammation [ 19 ]. Among the MMP genes, gelatinase A, encoded by the MMP2 gene, has been specifically correlated to tumor pathogenesis [ 20 , 21 ]. Furthermore, the MMP2 promoter contains several cis-acting regulatory elements, which modulate MMP2 expression through transcription factors, such as p53 and Sp1 [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main anticancer mechanism is the suppression of the COX-2 signaling pathway. The expression of COX-2 is associated with hepatocarcinogenesis by enhancing cell proliferation, apoptosis inhibition and angiogenesis induction (van Rees and Ristimaki, 2001; Hu, 2002; Sung et al , 2004; Wu, 2006; Liang et al , 2016). Indeed, Márquez-Rosado et al (2005) revealed the ability of NSAIDs to prevent hepatocarcinogenesis by suppressing COX-2 in mouse models.…”
Section: Discussionmentioning
confidence: 99%